Workplace health promotion, employee wellbeing and loyalty during covid-19 pandemic: Large scale empirical evidence from Hungary - Eva Gorgenyi-Hegyes; Robert Jeyakumar Nathan; Maria Fekete-Farkas (Economies, 2021)
Corporate social responsibility (CSR) has become an innovative strategic management tool of socially and environmentally conscious business organizations in the 21st century. Although external CSR activities are better researched, firms' internal CSR activities such as workplace health promotion and its impact on employee wellbeing are less understood, especially during a pandemic where job security is relatively lower in many sectors of employment. Additionally, wellbeing and good health have been recognized as important targets to achieve as part of the United Nation's Sustainable Development Goal 3. Therefore, this study investigates the relationship between health-related work benefits and employee wellbeing, satisfaction and loyalty to their workplace. Large scale survey research was performed with responses from 537 employees in Hungary and 16 hypotheses were tested. Data analysis and path modelling using PLS-SEM (Partial Least Squares Structural Equation Modelling) reveal two-layers of factors that impact employee wellbeing, satisfaction and loyalty. We term this as 'internal locus of control' and 'external locus of control' variables. Internal locus of control variables such as mental and emotional health leads to wellbeing at the workplace but do not directly impact employee satisfaction and loyalty. In contrast, external locus of control factors such as healthcare support leads to wellbeing, satisfaction and loyalty. Employer commitment to healthcare support system is found pertinent especially during the pandemic. We discover wellbeing as a unique standalone construct in this study, which is vital as is it formed by mental and emotional wellbeing of employees, albeit not a determinant of employee workplace satisfaction and loyalty. We theorize workers' self-reliance and preservation as possible explanations to the disassociation between employee wellbeing and loyalty to workplace during times of crisis and the pandemic.
Keywords: 330; COVID-19; CSR; employee satisfaction; employee wellbeing; PLS-SEM; SDG Goal 3; self-reliance and preservation; social sustainability; workplace health promotion